204k views
1 vote
F(x)=x^3+2x^2-6x+9

when f(x) is divided by x+a, the remainder is R, when divided by x-a, the reminder is 2R
a) show that 3a^3-2a^2-18a-9=0
b) solve the expression completely

User Lourenco
by
5.1k points

1 Answer

7 votes

Answer:

Explanation:

F(x)=x^3+2x^2-6x+9 when f(x) is divided by x+a, the remainder is R, when divided by-example-1
F(x)=x^3+2x^2-6x+9 when f(x) is divided by x+a, the remainder is R, when divided by-example-2
F(x)=x^3+2x^2-6x+9 when f(x) is divided by x+a, the remainder is R, when divided by-example-3
User Tertium
by
5.6k points